INTELLECTUAL SYSTEM FOR CALCULATING PERSONALIZED DRUG DOSAGES - Hamidullo Oybekov; Fazliddin Arzikulov (Modern American Journals, 2026)
This innovative project is dedicated to the creation of an intelligent system designed to determine the individualized dose of drugs. The system automatically determines the optimal dose of the drug, taking into account the patient's age, weight, physiological state, concomitant diseases, genetic characteristics, and individual sensitivity to drugs. It is based on modern artificial intelligence algorithms, statistical modeling and machine learning methods, as well as clinical databases. The use of the system increases the effectiveness of drugs, reduces side effects, and provides personalized medical care. At the same time, the system simplifies the work of doctors and reduces the likelihood of errors in the process of prescribing drugs. This intelligent solution is noteworthy as one of the important directions in the development of digitalization in healthcare and the transition to personalized medicine.
Keywords: Personalized drug dosing, intelligent system, artificial intelligence, machine learning, individual therapy, pharmacokinetics, pharmacodynamics, clinical decision support, personalized medicine, medical information systems.